The Utilization of Social Media in the Young Farmer Group in Cicarulang Village - Dedy Yusuf Aditya; Ai Solihah; Muhammad Tri Habibie (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
he purpose of this community service activity is to provide training to young farmer groups in Cicarulang village on the use of social media such as Instagram, Whatsapp and Facebook as a means to better market agricultural products, so that they get the best selling price, and to expand their agricultural product market. The method used in this service activity was online training and workshops which were done in two stages. This training was held collaborativelly by Cicarulang young farmer groups and Indraprasta PGRI University. The result of the activity is the improvement of participants’ ability in how to create good and attractive social media accounts, to manage business-based social media accounts as well as to create good marketing content such as making photos and interesting sentences to advertise their products.